2020
DOI: 10.3390/ma14010079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multi-Walled Carbon Nanotubes on Strength and Electrical Properties of Cement Mortar

Abstract: This work aims to investigate the effects of multi-walled carbon nanotubes (MWCNTs) on the strength and electrical properties of cement mortar. MWCNTs were added to cement mortar in four different concentrations: 0.00 wt.%, 0.01 wt.%, 0.015 wt.%, and 0.02 wt.% by the mass of cement. The consistency, density, setting time and compressive and flexural strength of mixes were tested and analyzed at 28 and 90 days curing time. Mechanical performance tests confirm an increase of 25% and 20% in the ultimate compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In the case of electrical properties of the composite materials, the literature review revealed that the test results are more consistent. For instance, Cerro-Prada et al [ 31 ] found that electrical resistivity of mortars with 0.01 and 0.015 wt.% MWCNTs resulted up to 10% decrease at both 28- and 90-days curing. Jang et al [ 32 ] found that the electrical conductivity of 0.5 wt.% MWCNT/cement pastes with/without surfactant was about 50% and 20% higher, respectively, than the electrical conductivity of plain cement paste.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of electrical properties of the composite materials, the literature review revealed that the test results are more consistent. For instance, Cerro-Prada et al [ 31 ] found that electrical resistivity of mortars with 0.01 and 0.015 wt.% MWCNTs resulted up to 10% decrease at both 28- and 90-days curing. Jang et al [ 32 ] found that the electrical conductivity of 0.5 wt.% MWCNT/cement pastes with/without surfactant was about 50% and 20% higher, respectively, than the electrical conductivity of plain cement paste.…”
Section: Resultsmentioning
confidence: 99%
“…The table shows that MWCNTs were relatively better in terms of their tensile strength than SWCNTs, while SWCNTs were better in thermal and electrical conductivity than MWCNTs. Many studies [ 22 , 23 , 24 , 25 , 26 ] also investigated the effect of CNTs on cement composite or concrete performance when CNTs were additionally mixed. Silvestro and Gleize [ 22 ] reviewed the existing studies regarding the effect of CNTs on the compressive strength and flexural strength of cement-based material.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee et al [24] found that the simultaneous addition of dispersed MWCNTs solution and MWCNTs base film to cement composites was able to better enhance the heating properties of the cement paste and obtain the lowest resistance. Cerro-Prada et al [25] studied the effect of four different mass fractions of MWCNTs on the strength and electrical properties of cement mortars. It was found that the resistivity of cement mortars decreased by 10% at both 0.015 wt% and 0.01 wt% dosing.…”
Section: Introductionmentioning
confidence: 99%